2021
DOI: 10.1542/peds.2021-052046
|View full text |Cite
|
Sign up to set email alerts
|

Transition to a Safe Home Sleep Environment for the NICU Patient

Abstract: Of the nearly 3.8 million infants born in the United States in 2018, 8.3% had low birth weight (<2500 g [5.5 lb]) and 10% were born preterm (gestational age of <37 completed weeks). Many of these infants and others with congenital anomalies, perinatally acquired infections, and other disease require admission to a NICU. In the past decade, admission rates to NICUs have been increasing; it is estimated that between 10% and 15% of infants will spend time in a NICU, representing approximately 500 000 neonates ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 235 publications
(228 reference statements)
0
3
0
Order By: Relevance
“…The American Academy of Pediatrics recommends infants be positioned supine when sleeping, which has been shown to decrease the incidence of sudden infant death syndrome. 22 It is also recommended that safe home sleep practices are used in the NICU when there are no medical contraindications and that safe sleep is modeled for parents, 23 yet many NICUs do not adhere to safe sleep recommendations. 24 , 25 Preintervention data gathered from a Level IV NICU for a recent quality improvement study showed that 87% of infants were in an unsafe sleep environment.…”
Section: Discussionmentioning
confidence: 99%
“…The American Academy of Pediatrics recommends infants be positioned supine when sleeping, which has been shown to decrease the incidence of sudden infant death syndrome. 22 It is also recommended that safe home sleep practices are used in the NICU when there are no medical contraindications and that safe sleep is modeled for parents, 23 yet many NICUs do not adhere to safe sleep recommendations. 24 , 25 Preintervention data gathered from a Level IV NICU for a recent quality improvement study showed that 87% of infants were in an unsafe sleep environment.…”
Section: Discussionmentioning
confidence: 99%
“…Several standardized programs have been successful and include policies consistent with the AAP recommendations on sleep safety, education for providers and families, visible prompts, modeling of safe sleeping while in the hospital, algorithms for assessment of readiness for safe sleep readiness, and quality improvement audits during hospitalization and postdischarge. The AAP (Goodstein et al, 2021) report provides detailed recommendations for each of the clinical issues discussed, the messages for all conditions are consistent and strong. Although there are commonly used therapeutic interventions used in the treatment of NICU patients that are not consistent with home infant sleep safety, use of these therapeutic interventions should be minimized as much as is medically feasible and when necessary, should be discontinued as soon as possible (Goodstein et al).…”
mentioning
confidence: 99%
“…The latest AAP report (Goodstein et al, 2021) provides an in-depth review of literature on the relationship between the clinical issues of respiratory distress, apnea, hyperbilirubinemia, gastroesophageal refl ux, and neonatal opioid withdrawal syndrome and how care techniques, specifi cally nonsupine positioning as well as swaddling and skin-to-skin care, affects infant sleep safety. As the majority of NICU patients commonly require care that is inconsistent with safe sleep recommendations, it is understandable that providers and parents can easily become confused.…”
mentioning
confidence: 99%